Labour and Politics in Canada and Australia: Towards a Comparative Approach to Developments to 1960 - Irving, Terry; Seager, Allen (Labour/Le Travailleur, 1996)
This chapter seeks to move the discussion of labour and politics beyond the contest of political ideologies in the movement and the constraints of the liberal democratic state. To explain the different political histories of the Australian and Canadian movements we use a model with three dimensions: the changing balance between labour and politics; the different social forces that labour seeks to represent; and the different conceptions of politics that labour holds. After a discussion of the literature on labour and politics in the two countries, the paper applies this model to distinguish two periods, a formative period up to the early 1920s, in which labour entered politics, and the period from the 1920s to the 1950s when parties or governments took politics into the labour movement. The model enables us to characterize the politics of the Australian Labor Party as a form of class-based labourism, with significant moments of working-class socialism. We characterize the Co-operative Commonwealth Federation/New Democratic Party as a form of populist socialism. The paper concludes with some insights gained from using a common model in a comparative exercise.